2007
DOI: 10.1111/j.1524-4725.2007.34010.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Dye Laser Treatment is Effective in the Treatment of Recalcitrant Viral Warts

Abstract: Pulsed dye laser treatment is effective and safe in the treatment of recalcitrant viral warts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 25 publications
0
29
0
2
Order By: Relevance
“…For another thing, many dermatologists who mostly provide laser therapy have veered away from conventional dermatology and are dedicated to the therapy of cosmetic indications and “treatment” of patients with body dysmorphic disorders. This might be why their interest in treatments of inflammatory dermatological diseases such as CLE and other, not primarily cosmetic–aesthetic dermatological indications seems to have diminished 8–12 …”
mentioning
confidence: 99%
“…For another thing, many dermatologists who mostly provide laser therapy have veered away from conventional dermatology and are dedicated to the therapy of cosmetic indications and “treatment” of patients with body dysmorphic disorders. This might be why their interest in treatments of inflammatory dermatological diseases such as CLE and other, not primarily cosmetic–aesthetic dermatological indications seems to have diminished 8–12 …”
mentioning
confidence: 99%
“…Interestingly, PDL has the highest RFI rate, with 74% of patients without recurrences after 6 months. Previous studies showed the importance of PDL for the lowest rate of adverse event, as compared with other lasers, and for the treatment of recalcitrant warts . Nevertheless, considering the availability, costs and the absence of guidelines for PDL, other treatment options should be taken into account even if affected by a 3‐fold higher risk of recurrence (keratolytics and CO 2 laser).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we assessed the treatment efficacy on recalcitrant warts in this study, which have an expected lower cure rate than simple warts. Several uncontrolled studies have found PDL able to clear 48-93% of simple and/or recalcitrant warts at various locations, and two studies have reported of low cure rates at 0% and 6.5% of warts [5][6][7][8][9][10][11][12][13]15,17,18]. Cure rates observed in these non-randomized, non-controlled studies do not account for the spontaneous resolution of warts and the high risk of bias makes interpretation and validity of these outcomes uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Newer, non-destructive interventions such as the pulsed dye laser (PDL) and intense pulsed light (IPL) have been suggested for treatment of recalcitrant warts [5][6][7][8][9][10][11][12][13][14][15]. The mechanism of action is assumed to be selective destruction of superficially papillary capillaries of the wart as well as thermal injury of the heat-sensitive HPV [5].…”
Section: Introductionmentioning
confidence: 99%